2021
DOI: 10.7759/cureus.15179
|View full text |Cite
|
Sign up to set email alerts
|

Model of End-Stage Liver Disease (MELD) Score as a Predictor of In-Hospital Mortality in Patients with COVID-19: A Novel Approach to a Classic Scoring System

Abstract: Background Limited data is available for reliable and accurate predictors of in-hospital mortality in patients diagnosed with COVID-19. Methods This scientific study is a retrospective cohort study of patients without a known history of liver diseases who were hospitalized with COVID-19 viral infection. Patients were stratified into low score groups (Model of End-Stage Liver Disease [MELD] score <10) and high score groups (MELD ≥10). Clinical outcomes were evaluated, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
1
10
2
Order By: Relevance
“…It has been hypothesized earlier in the pandemic that patients taking ACE inhibitors or angiotensin receptor blockers would be at a higher risk of adverse clinical outcomes; however, later studies have refuted this hypothesis [17,18]. In addition, COVID-19 is associated with myocardial injury [19,20], thrombocytopenia [21,22], and liver dysfunction [23][24][25][26][27] which predicts higher mortality in the general population and in patients with HF [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized earlier in the pandemic that patients taking ACE inhibitors or angiotensin receptor blockers would be at a higher risk of adverse clinical outcomes; however, later studies have refuted this hypothesis [17,18]. In addition, COVID-19 is associated with myocardial injury [19,20], thrombocytopenia [21,22], and liver dysfunction [23][24][25][26][27] which predicts higher mortality in the general population and in patients with HF [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Additional laboratory abnormalities, such as neutrophil-to-lymphocyte ratio, troponin-I, and abnormal liver function tests, have also been associated with increased mortality and adverse outcomes, which can be further explored in future studies. 22–27 …”
Section: Discussionmentioning
confidence: 99%
“…While our study was conducted, few studies were had already evaluated the relationship between in-hospital (short-term) mortality o, length of intensive care, length of hospital stay, and long-term mortality of COVID-19 and the MELD-XI score [26][27] . In one of these studies, a higher MELD-XI score was found to be associated with mortality in COVID-19 patients without liver disease, and it was stated that it could be a helpful tool for other risk modalities 26 . In another study, it was shown that the MELD-XI score may be useful in predicting early mortality in the elderly and critically ill patients 27 .…”
Section: Discussionmentioning
confidence: 99%